Pengaruh Pengetahuan Anggaran Anggota Dewan Terhadap Pengawasan Keuangan Daerah Dengan Partisipasi Masyarakat Sebagai Variabel Moderating (Studi Pada Anggota DPRD Kabupaten Tolitoli) - ayuwandira morad; Abd Rahman Alatas; Risman Risman (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
This study aims to determine and analyze the effect of Budgetary Knowledge of Council Members on Regional Financial Supervision in Tolitoli Regency with Community Participation as a moderating variable. This study uses a quantitative research approach design, namely research that describes in detail the effect of the Knowledge of Council Members on Budgeting on Regional Financial Supervision in Tolitoli Regency with Community Participation as an intervening variable. This type of research is used to develop concepts and collect facts and test hypotheses. Sources of data in the form of primary and secondary data, namely primary data are data from interviews and research questionnaires and secondary data are data obtained indirectly such as documentation data, articles, and organizational structure. Based on the research and discussion results, it can be concluded that the Budgetary Knowledge of Council Members has a significant effect on Regional Financial Supervision in Tolitoli Regency. Regional Financial Supervision affects the Absolute Residual value so that it can be said that Community Participation (Z) moderates the relationship between Council Member Knowledge (X) and Regional Financial Supervision (Y). Keywords : Budget knowledge of council members, regional financial supervision, community participation